Attitude towards Labor Migration from Post-Soviet Economies among the Population of Central Siberia (Krasnoyarsk Krai Case Study) - Koptseva, Natalia P.; Kirko, Vladimir I.; Petrishchev, Vladimir I. (International Journal of Economics and Financial Issues, 2016)
Between 2010 and 2016, scientists and post-graduates from the Siberian Federal University have conducted a number of complex studies into the processes of labor migration in Krasnoyarsk Krai. These studies involved field research methods, surveying, expert interviews, statistical data analysis, and the associative experiment method designed by A. Nazarov and R. Sokolov. Based on these studies, the researchers were able to conclude that migration processes were taking contradictory paths. The new industrialization of Siberia requires substantial labor resources and Krasnoyarsk Krai needs a significant increase in manpower. Job-wise, the Central Siberian regions appear to look most attractive to people living in post-Soviet economies. The ethnic composition of the migrant workforce coming to Krasnoyarsk Krai has seen a substantial change over the past 10 years. At the same time, anti-migrant attitudes in Krasnoyarsk Krai are on the rise, whilst ethnic and religious tolerance is decreasing. Keywords: economic migration, labor migration, Siberia, Krasnoyarsk Krai, anti-migrant attitudes JEL Classifications: F6, J7, Z1